Dayside Cusp Aurorae and Ionospheric Convection Under Radial Interplanetary Magnetic Fields. Issue 5 (12th May 2021) - Li, Hsien‐Ming; Shue, Jih‐Hong; Taguchi, Satoshi; Nosé, Masahito; Hosokawa, Keisuke; Ruohoniemi, J. Michael; Zhang, Yongliang; Wing, Simon; Lester, Mark
Abstract: Dayside cusp aurorae are created from particles precipitating into the cusp, and ionospheric convection is driven by solar wind electric fields. In this study, we coordinated the observations obtained from the all‐sky camera on Svalbard, the Super Dual Auroral Radar Network, SuperMAG magnetometer data, and far ultraviolet imagers on board the Defense Meteorological Satellite Program satellites for the event January 4, 2014 to examine the morphology of aurorae and the patterns of ionospheric convection for radial interplanetary magnetic field (IMF). During the event, a poleward‐moving auroral form and antisunward ionospheric convection were observed when the IMF turned into almost purely radial. Moreover, both types of antisunward and sunward convection were simultaneously observed near the footprint of the cusp at different times during the radial IMF period. The antisunward convection and sunward convection are typically an indicator of the dayside reconnection for the southward IMF and the lobe reconnection for the northward IMF, respectively. All those observations support the concept of low‐latitude dayside and high‐latitude lobe reconnection for the radial IMF. This study further shows that the coexistence of the two types of reconnection for radial IMF, resulting in an interplay of repetitive antisunward and sunward convection. Plain Language Summary: The event for January 4, 2014 enables us to study the features of dayside cusp aurorae and ionospheric convection for the radial IMF. During the event, a poleward‐moving auroral form and antisunward convection were observed near the footprint of the cusp, which provides indirect evidence of the magnetic reconnection that occurs at the dayside magnetopause for the radial IMF. S‐shaped aurorae, named from their morphology, near the cusp were also observed during the event. This type of aurora was possibly created by magnetosheath plasma jets impinging on the surface of the magnetopause or magnetic reconnection occurring locally on the magnetopause. For ionospheric convection, the primary convection pattern for the radial IMF was similar to that for the southward IMF, particularly for antisunward convection near the cusp. However, sunward convection near the cusp was also observed at the same time, indicating the lobe reconnection coexists with the dayside reconnection. In summary, the features of dayside cusp aurorae and ionospheric convection for the northward and southward IMFs can be seen at different times during the radial IMF event. Key Points: A period of almost purely radial interplanetary magnetic field (IMF) (cone angle < 3°) was embedded in the radial IMF event for January 4, 2014 IMF B y or B z related poleward‐moving aurora was created by precipitating electrons along the open field lines in the cusp during the period The antisunward ionospheric convection became stable and consistent with magnetometer observations when the IMF was almost purely radial